A two-step solid-state reaction to synthesize the yellow persistent Gd3Al2Ga3O12:Ce3+ phosphor with an enhanced optical performance for AC-LEDs. Issue 77 (6th September 2017) - Liu, Yong-Fu; Liu, Pu; Wang, Lei; Cui, Cai-E; Jiang, Hao-Chuan; Jiang, Jun
Abstract : The internal quantum efficiency of the GAGG:Ce 3+ persistent phosphor was enhanced to 82% by our proposed two-step reaction method. Abstract : By using a two-step solid-state reaction to synthesize the yellow-persistent Gd3 Al2 Ga3 O12 :Ce 3+ phosphor, both the luminescence and afterglow properties were greatly enhanced. Its internal quantum efficiency reaches as high as 81.9%, indicating its promising application in reducing the flicker effect in AC-LED-based white light systems.